The Effect of Relationship Marketing Implementation on Depositor Customer Loyalty at BSI KCP Gunung Tua North Padang Lawas - Siti Hot Nita Hasibuan; Rahmi Syahriza; Nursantri Yanti (Dinasti Publisher, 2024)
The need for banks to retain and acquire new customers amid an increasingly competitive business environment drives this research. Using Relationship Marketing, a marketing approach that emphasizes long-term relationships with clients, is one way to increase customer loyalty. The purpose of this study is to find out how relationship marketing includes communication, trust, commitment, and handling complaints against BSI KCP Gunung Tua customer loyalty. This study used quantitative methodology, with data analysis carried out by correlation analysis between variables and statistical analysis using SPSS version 23 analysis tools, which include: Validity test, normality test, classical assumption test, and hypothesis test conducted using a sample of 100 respondents obtained with the Slovin technique. Bank interviews and questionnaires were used to collect data for the study. Research findings show that complaint handling, communication, dedication, and trust all play a role in fostering client loyalty. The results of multiple linear regression analysis showed that, while other factors not addressed in this study contributed to the remaining 23.5% of the effect, the four Relationship Marketing variables together had a significant effect of 76.5% on customer loyalty.